Computing in Civil Engineering 2019 : Data, sensing, and analytics : selected papers from the ASCE International Conference on Computing in Civil Engineering 2019, June 17-19, 2019, Atlanta, Georgia - Cho, Yong Kwon; Leite, Fernanda; Behzadan, Amir; Wang, Chao, Ph. D. (American Society of Civil Engineers, 2019)
This collection contains 77 peer-reviewed papers on data, sensing, and analytics presented at the ASCE International Conference on Computing in Civil Engineering 2019, held in Atlanta, Georgia, June 17-19, 2019. Topics include: big data and machine learning; reality capture technologies; LiDAR and RGB-D; and robotics, automation, and control.This proceedings will be of interest to researchers and practitioners working with emerging computing technologies in a wide range of civil and construction engineering applications.